Using GRASP for designing a layered network: a real IP/MPLS over DWDM application case. (1st January 2013) - Risso, Claudio; Robledo, Franco
In this paper, we study a network design problem arising from the deployment of an IP/MPLS network over an existing transport infrastructure. The goal is to find a minimum cost installation of links such that traffic demands can resiliently be accomplished. In this paper, an integer programming formulation and metaheuristic are presented. This work is based on a real application case for a telecommunications company. The results allowed the company to reduce over 30% of the infrastructure costs.